Westonci.ca is your go-to source for answers, with a community ready to provide accurate and timely information. Our platform offers a seamless experience for finding reliable answers from a network of knowledgeable professionals. Discover in-depth answers to your questions from a wide network of professionals on our user-friendly Q&A platform.

solve using the quadratic formula:
3x=2x^2-2


Sagot :

Answer:

[tex]x=2\\x=-\frac{1}{2}[/tex]

Step-by-step explanation:

1) Move terms to the left side.

[tex]3x=2x^{2} -2\\3x-(2x^{2}-2)=0[/tex]

2) Distribute.

[tex]3x-(2x^{2} -2)=0\\3x-2x^{2} +2=0[/tex]

3) Rearrange terms.

[tex]3x-2x^{2} +2=0\\-2x^{2} +3x+2=0[/tex]

4) Common factor.

[tex]-2x^{2} +3x+2=0\\-(2x^{2} -3x-2)=0[/tex]

5) Divide both sides of the equation by the same term.

[tex]-(2x^{2} -3x-2)=0\\2x^{2} -3x-2=0[/tex]

6) Use the quadratic formula.

[tex]x=\frac{-b+\sqrt{b^{2}-4ac } }{2a}[/tex]

Once in standard form, identify a, b, and c from the original equation and plug them into the quadratic formula.

[tex]2x^{2} -3x-2=0\\a=2\\b=-3\\c=-2[/tex]

[tex]x=\frac{-(-3)+\sqrt{(-3)^{2} -4*2(-2)} }{2*2}[/tex]

7) Simplify.

Evaluate the exponent

[tex]x=\frac{3+\sqrt{(-3)^{2}-4*2(-2) } }{2*2}[/tex]

[tex]x=\frac{3+\sqrt{9-4*2(-2)} }{2*2}[/tex]

Multiply the numbers

[tex]x=\frac{3+\sqrt{9-4*2(-2)} }{2*2}[/tex]

[tex]x=\frac{3+\sqrt{9+16} }{2*2}[/tex]

Add the numbers

[tex]x=\frac{3+\sqrt{9+16} }{2*2}[/tex]

[tex]x=\frac{3+\sqrt{25} }{2*2}[/tex]

Evaluate the square root

[tex]x=\frac{3+\sqrt{25} }{2*2} \\x=\frac{3+5}{2*2}[/tex]

Multiply the numbers

[tex]x=\frac{3+5}{2*2}[/tex]

[tex]x=\frac{3+5}{4}[/tex]

8) Seperate the equations.

To solve for the unknown variable, separate into two equations: one with a plus and the other with a minus.

[tex]x=\frac{3+5}{4}[/tex]

[tex]x=\frac{3-5}{4}[/tex]

9) Solve.

Rearrange and isolate the variable to find each solution.

[tex]x=2\\x=-\frac{1}{2}[/tex]